Implementasi Metode Decision Tree Pada Sistem Penunjang Keputusan Penerimaan Karyawan Bank - Izmy Alwiah Musdar; Syamsul Bahri; Baizul Zaman (JTRISTE, 2017)
One of the way that company do to get qualified employees is to select the candidates by selection process. In order to perform employee selection more efficient and to avoid the subjectivity of the decision, a Decision Support System (DSS) is required to assist the Human Resource Manager to make the decision making. This research uses Decision Tree method to determine the choice. The results show there are 2 of the 20 test data that is false in prediction. Prediction accuracy is calculated using confusion matrix and the accuracy is 0.9.